2022
DOI: 10.3390/v14051055
|View full text |Cite
|
Sign up to set email alerts
|

Senecavirus A Enhances Its Adaptive Evolution via Synonymous Codon Bias Evolution

Abstract: Synonymous codon bias in the viral genome affects protein translation and gene expression, suggesting that the synonymous codon mutant plays an essential role in influencing virulence and evolution. However, how the recessive mutant form contributes to virus evolvability remains elusive. In this paper, we characterize how the Senecavirus A (SVA), a picornavirus, utilizes synonymous codon mutations to influence its evolution, resulting in the adaptive evolution of the virus to adverse environments. The phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Due to the low-fidelity characteristics of SVA RdRp, SVA displays a relatively high mutation rate during serial passaging in vitro , as demonstrated by our previous study ( 17 ). Therefore, SVA can rapidly enhance its own adaptive ability via synonymous codon bias evolution ( 18 ). Indeed, the codon preference analysis has indicated that natural selection is a primary driving force that affects the codon usage bias in SVA ( 15 ).…”
Section: Selective Pressure Prompting Sva Evolutionmentioning
confidence: 99%
“…Due to the low-fidelity characteristics of SVA RdRp, SVA displays a relatively high mutation rate during serial passaging in vitro , as demonstrated by our previous study ( 17 ). Therefore, SVA can rapidly enhance its own adaptive ability via synonymous codon bias evolution ( 18 ). Indeed, the codon preference analysis has indicated that natural selection is a primary driving force that affects the codon usage bias in SVA ( 15 ).…”
Section: Selective Pressure Prompting Sva Evolutionmentioning
confidence: 99%
“…Each point in the plot represents the position of the corresponding gene. It was used to analyze the correlation between GC 12 and GC 3 , and to judge the factors affecting the preference for codon usage (Zhao et al 2022). In the regression curve, natural selection dominates when the slope of the regression curve approaches 0, while the mutational pressure plays the main role if the slope approaches 1 (Zhang et al 2022 Parity rule 2 (PR 2 )-plot analysis…”
Section: Neutral Plotting Analysismentioning
confidence: 99%
“…One of the insights into RNA viruses' evolution is that synonymous codon usage generally follows a nonrandom and species-specific pattern [15][16][17][18][19][20][21][22]. The relevant investigations indicate that synonymous codon changes without altering the primary amino acid sequence are influenced by multiple selective forces.…”
mentioning
confidence: 99%